Choroidal metastasis: Impact of primary tumors and age on survival - a single center analysis - Philipp Fuchs; Adrian Reumueller; Judith Kreminger; Elena Zafeiri; Stefan Sacu; Reinhard Told; Roman Dunavoelgyi (PLoS ONE, 2026)
Purpose The purpose of this study was to determine whether patient’s age and their primary tumor type act as independent predictors of their survival after a diagnosis of choroidal metastasis. Methods This retrospective single-center study (August 2013 – August 2025) included 70 patients with choroidal metastases. Clinical data and multimodal imaging were extracted from medical records. Tumor volume was calculated from ultrasound measurements. Patients were grouped according to primary tumor origin (lung, breast, or other primaries). Survival was compared between these three primary tumor groups and according to age. Group differences in continuous variables were assessed using ANOVA/Kruskal-Wallis testing, and survival distributions were analyzed with Kaplan-Meier curves. Patients were categorized into younger (<59.6 years) and older (≥59.6 years) groups for Kaplan-Meier survival analysis. Univariate and multivariate Cox regression models were performed to identify independent predictors of overall survival. Results Median overall survival was 71.6 weeks. Statistically significantly longer survival was found in patients <59.6 years (median 88.3 weeks; estimated 3-year survival 33.2%) compared with those ≥59.6 years (median 41.9 weeks; 3-year survival 16.8%; p = 0.037. Primary tumor group analysis showed a median survival of 94.4 weeks for breast cancer (estimated 3-year survival 38.3%), 52.7 weeks for lung cancer (9,5%), and 40.6 weeks for other primaries (19.7%). However, this difference was not statistically significant (p = 0.269). In multivariate Cox regression analysis, age ≥ 59.6 years (HR 2.10; p = 0.016) and >1 extraocular metastases elsewhere in the body (HR 2.53; p = 0.029) were independent predictors of mortality. Conclusion Survival in choroidal metastases is strongly driven by age and the number of extraocular metastatic sites at presentation. Our findings suggest that younger age and a lower metastatic burden are most reliable indicators for a more favorable prognosis.